(untitled) (Research, Society and Development, 2022)
This work proposes to analyze the importance of strategic planning for companies, in achieving objectives and goals within the organization and even in decision-making, aiming at the success of the company. With the market in permanent change, the company, aiming to achieve its developed objectives and goals, perceiving changes, will direct its strategies. In this context, it is worth mentioning that the future success of a company, nowadays, is closely linked with strategic planning and its non-development can cause decisive impacts for failure.